Climate and geographical influence on the performance of infiltration-based facilities for managing runoff – Temporal and spatial variability - Mantilla, Ivan (Luleå tekniska universitet, Arkitektur och vatten, 2024)
Climate change is expected to lead to more intense and severe rainfall events in the future, significantly increasing the risk of urban flooding. This change, characterized by spatial and temporal shifts in precipitation patterns, presents a challenge to the capacity of existing urban drainage systems, which may lead to higher runoff volumes than they were initially designed to handle. Relying solely on enlarging stormwater infrastructure to tackle this issue could be expensive and may transfer the flooding risk downstream, rather than effectively resolving it. Furthermore, climate change may also lead to prolonged dry spells, potentially resulting in soil compaction and diminished soil infiltration rates. Given these considerations, it is essential to ensure urban drainage systems are both adaptable and space-efficient, with an enhanced capacity to manage the heightened rainfall caused by climate change. As awareness of the hydrological and environmental impacts of urbanization on catchments grows, there has been a paradigm shift toward adopting green infrastructure solutions. These approaches diverge from traditional 'end-of-pipe' strategies, emphasizing more holistic and sustainable methods. The overall aim of this thesis is to investigate the implications of climatic conditions and geographic location on the retention and detention capacity of three types of infiltration-based facilities: a biofilter cell, a green roof, and a grass swale. A rainfall-runoff model of a biofilter cell and a green roof, combined with swale irrigation experiments, was used to evaluate the capacity of these facilities to reduce runoff volumes and attenuate peak flows. The analysis was conducted in four urban areas representing oceanic (Cfc), humid continental (Dfb), and subarctic (Dfc) climatic zones. The assessment also includes the effect of temporal and spatial variation of saturated hydraulic conductivities (ksat). Swale irrigation experiments were conducted to evaluate the effect of outflow controls on swale retention and ...